2012
DOI: 10.1007/s10926-012-9390-0
|View full text |Cite
|
Sign up to set email alerts
|

How do Older Employees with Health Problems Remain Productive at Work?: A Qualitative Study

Abstract: The influence that health can have on productivity depends on the individuals' unique imbalance and personal disposition. Helpful a priori work place characteristics and personal well-being should be promoted so that a balance between demands and resources can be found in times of poor health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…We hypothesize that the subgroup of workers with chronic disease is responsible for the associations found between job strain and early exit from work. This is supported by a recent qualitative study in older workers, where it was concluded that the influence of health on productivity depends on the balance between demands and resources [34]. In this sense, our results suggest that having a chronic disease may trigger the imbalance between demands and resources.…”
Section: Differences and Similarities Between Workers With And Withousupporting
confidence: 89%
“…We hypothesize that the subgroup of workers with chronic disease is responsible for the associations found between job strain and early exit from work. This is supported by a recent qualitative study in older workers, where it was concluded that the influence of health on productivity depends on the balance between demands and resources [34]. In this sense, our results suggest that having a chronic disease may trigger the imbalance between demands and resources.…”
Section: Differences and Similarities Between Workers With And Withousupporting
confidence: 89%
“…This could be because the productivity at work measure used in this study was not specifically health-related productivity loss, ie, presenteeism. Productivity is an output that can be influenced both by the individual him-or herself as well as by tangible devices (eg, computers) or social factors (eg, cooperative and productive colleagues) that are necessary for an individual to conduct his/her work productively (27). This supports the notion to study similarities and differences between general productivity loss at work and presenteeism.…”
Section: Discussionmentioning
confidence: 62%
“…This suggests that the effects of changes in health problems on work ability are most likely to occur in a shorter period of time, ie, within the same year, where after it is possible that adjustments are made. This is supported by findings from a qualitative study in a comparable study population, which showed that many adjustments were made in order to allow employees to cope with their health problems at work and restore a balance in their demands and resources (27).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Findings from past qualitative research (15,16) support the idea that work-related factors modify the effect of health on sickness absence, but quantification of this occurrence is still lacking in the literature. Understanding the effect of work on the influence of poor health on sickness absence has important practical implications because health problems may not always be solved, but work-related factors are amendable.…”
mentioning
confidence: 89%